Government of National Unity (GNU) as a strategy for democracy in Zimbabwe - Tumbare, D. T. (University of Limpopo, 2014)
Debate on GNU centres around whether or not as a tool/plan/strategy it promotes, cultivates and fosters democracy in situations where there is lack there-of. In other words does a GNU create the conditions or environment necessary for the establishment of democracy? Various studies have shown that GNU is popular as a conflict-resolution tool and that in countries where it has been employed, it has resulted in the successful cessation of violent conflict. This study explores GNU to find out how successful it was in democratic entrenchment in Zimbabwe. It revealed through interviews and secondary sources that in Zimbabwe GNU managed to bring together antagonistic political contenders to work together for the restoration of peace and democracy and nation-building. GNU did not however, guarantee permanent solution of the crisis. In other words there were other significant issues which could not simply be resolved through a GNU. Finally the study further explored the different reasons for GNU inability to resolve those issues in Zimbabwe.
Thesis (M.A. (International Politics)) --University of Limpopo, 2014
Keywords: Zimbabwe government; Democracy; Lawyers for human rights; 321.8096891; Zimbabwe -- Politics and government; Democracy -- Zimbabwe; Africa, Southern -- Politics and government